Exosomal miRNAs and lncRNAs: The Modulator Keys of Cancer-Associated Fibroblasts in the Genesis and Progression of Malignant Neoplasms - Villegas-Pineda, Julio César; Lizarazo-Taborda, Mélida del Rosario; Ramírez-de-Arellano, Adrián; Pereira-Suárez, Ana Laura (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment is made up of a universe of molecular and cellular components that promote or inhibit the development of neoplasms. Among the molecular elements are cytokines, metalloproteinases, proteins, mitochondrial DNA, and nucleic acids, within which the ncRNAs: miRNAs and lncRNAs stand out due to their direct modulating effects on the genesis and progression of various cancers. Regarding cellular elements, the solid tumor microenvironment is made up of tumor cells, healthy adjacent epithelial cells, immune system cells, endothelial cells, and stromal cells, such as cancer-associated fibroblasts, which are capable of generating a modulating communication network with the other components of the tumor microenvironment through, among other mechanisms, the secretion of exosomal vesicles loaded with miRNAs and lncRNAs. These ncRNAs are key pieces in developing neoplasms since they have diverse effects on cancer cells and healthy cells, favoring or negatively regulating protumoral cellular events, such as migration, invasion, proliferation, metastasis, epithelial-mesenchymal transition, and resistance to treatment. Due to the growing number of relevant evidence in recent years, this work focused on reviewing, analyzing, highlighting, and showing the current state of research on exosomal ncRNAs derived from cancer-associated fibroblasts and their effects on different neoplasms. A future perspective on using these ncRNAs as real therapeutic tools in the treatment of cancer patients is also proposed.